2013
DOI: 10.1371/journal.pone.0081874
|View full text |Cite
|
Sign up to set email alerts
|

Early Gene Expression Analysis in 9L Orthotopic Tumor-Bearing Rats Identifies Immune Modulation in Molecular Response to Synchrotron Microbeam Radiation Therapy

Abstract: Synchrotron Microbeam Radiation Therapy (MRT) relies on the spatial fractionation of the synchrotron photon beam into parallel micro-beams applying several hundred of grays in their paths. Several works have reported the therapeutic interest of the radiotherapy modality at preclinical level, but biological mechanisms responsible for the described efficacy are not fully understood to date. The aim of this study was to identify the early transcriptomic responses of normal brain and glioma tissue in rats after MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 50 publications
0
69
1
Order By: Relevance
“…The specific response of the tumor tissues is composed by 316 significantly modulated transcripts which are mainly related to immune/inflammatory response, as described in a previous study [35]. But there are other early biological processes underlying the differential effect of MRT on tumor and normal brain [34].…”
Section: Mrt Versus Broad Beam Irradiationmentioning
confidence: 72%
See 1 more Smart Citation
“…The specific response of the tumor tissues is composed by 316 significantly modulated transcripts which are mainly related to immune/inflammatory response, as described in a previous study [35]. But there are other early biological processes underlying the differential effect of MRT on tumor and normal brain [34].…”
Section: Mrt Versus Broad Beam Irradiationmentioning
confidence: 72%
“…MRT may also induce transcriptomic changes such as an overexpression of the resistance factor Areg which is critical for tumor survival and progression, as it involves tumor cell proliferation, invasiveness, motility, inhibition of apoptosis and angiogenesis [40]. Moreover, a strong involvement of immune and/or inflammatory responses after MRT has been revealed in several recent studies [34,35,39]. MRT effects on vasculature, tumor cell proliferation arrest and death, involvement of resistance mechanisms and immune response can all be studied separately but an integrated consideration of these mechanisms is now needed to understand the efficiency of MRT and to further increase the therapeutic potential of this promising method.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…CCL2 or monocyte chemotactic protein-1 (MCP-1), is the protein encoded by Ccl2, which has been shown to be upregulated by MRT in 9L brain tumors at 6 h postirradiation (15). CCL2 belongs to the CC chemokine family, and recruits monocytes to inflammatory sites in diseases such as psoriasis, rheumatoid arthritis and atherosclerosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have shown that normal tissues including the central nervous system (CNS) in animal models are extremely tolerant to MRT compared to CRT (9)(10)(11)(12)(13)(14)(15)(16). MRT at 150-625 Gy in-beam doses ablates tumors while apparently causing little or no damage to the surrounding normal tissues (17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Furthermore, potentially antioncogenic apoptotic proteomic changes indicate that the collective interaction of such MB irradiation-induced bystander effect proteins might confer a protective effect on normal tissues [20]. (6) Transcriptional gene expression analysis of intracerebral gliosarcomas in rats [12,29] and EM6.5 breast tumours in mice [30] have identified MRT induced immunity-related modulations, clearly different from transcriptional changes induced by unsegmented broad beams.…”
Section: Mrt In Small Animalsmentioning
confidence: 99%